Factors affecting the intention to fully adopt the computer assisted audit tools and techniques (CAATTs) among external auditors in Jordan - Khasawneh, Ayman Mohammad Said (School of Business Innovation and Technopreneurship, 2017)
The primary focus of the present research was to determine the constructs affecting the intention to fully adopt CAATTs. The study concentrated on external auditors in Jordan. The factors examined were performance expectancy, effort expectancy, social influence, facilitating conditions, and trust. Furthermore, the study was limited to Jordanian external auditors (98) working in the Big 4, international, and national firms in the north, middle, and south of Jordan. These locations were selected for the present study because of the high number of auditors working in these areas especially in the middle region where the capital city of Jordan is located.